Analisa Geopressure Pada Sumur Gas Lapangan Sumatera Utara Untuk Evaluasi Problem Partial Loss Pada Trayek 8 Â½" - Ade Indra Gurada Capah; Muhammad Akbar Najib; Reinaldi Juniarto (Jurnal Migasian, 2020)
The drilling of well â€œXâ€ experienced a delay in reaching the target due to obstacles. Most of the non-productive time is caused by problems of well instability such as partial loss. well instability occurs when the mudweight used does not match the geopressure model of the well so that it is not optimal. The use of mudweight in well "X" is based on the geopressure model without a safe mud window approach from the nearest well where the well is located far enough away that it is less relevant to be used as a reference. Mudweights used are 14.5 - 14.9 ppg on the trajectory hole 8 1/2 ". Geopressure analysis is carried out using the help of Drillwork Predict Software. Geopressure components to be estimated are overburden pressure, pore pressure, fracture pressure, horizontal stresses and collapse pressure. After analyzing the geopressure model, the safe mud window can be identified, and analysis of the drilling problems that occur by examining the actual mudweight usage data and formation lithology data can be done. The optimal mud weight to minimize well instability must be greater than collapse pressure but not more than the minimum in situ stress. From the results of the geopressure analysis carried out, it can be concluded that there is overpressure at a depth of 890 m / 1279.5 ft due to disequilibrium compaction. On trajectory hole 8 1 / 2 "the mud weight used is too large, causing partial loss. Based on the safe mud window obtained from geopressure analysis of well X, the optimal mud weight design is 14.67 - 15.4 ppg for drilling on the trajectory hole 8 1/2 ".